ANALISIS KONDISI FUNGSIONAL RUAS JALAN JENU-MERAKURAK DENGAN MENGGUNAKAN METODE PSI DAN RCI SERTA PREDIKSI SISA UMUR PERKERASAN JALAN (REMAINING LIFE) - Sugiyanto; Arifin Nur Ahmad (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2022)
This research was conducted with the aim of analyzing the functional condition of the Jenu-Merak Urak road. On roads with construction using flexible pavement (asphalt roads) and having a length of 5.3 kilometers or 3.29 miles, the analysis is based on the road grade or IRI (international roughness index) obtained on the observation of the road. The parameters used are indices related to the level of road safety/performance (riding quality) and the estimated remaining service life of the road. The results of this study obtained the results of a functional analysis of the road based on the road condition index of 7.75. It can be stated that the condition of the analyzed road surface is very good and generally evenness. Likewise, the results of road functional analysis based on road service conditions (present serviceability index) of 4.03 can be stated that the condition of the analyzed road service functions is classified as good. Based on data, the actual increase in traffic (3.05%/year) compared to the planned (2.7%/year) resulted in the prediction of the remaining pavement life (remaining life) of the analyzed road, the design life of the road ending 3 (three) years earlier than planned age. The analysis results obtained in this study can prove that there is a correlation and does not stand alone between the results of the analysis of road surface conditions that are classified as good and generally evennes will produce road service conditions that are classified as good as well.